Peran Blockchain dalam Akuntansi Sektor Publik: Analisis Bibliometrik - Desiana Rachmawati; Dwike Rachmaningtyas; Rischa Inung Fauziah; Fandi Galang Wicaksana (Balance : Jurnal Akuntansi dan Bisnis, 2026)
This study maps the development and research direction of blockchain applications in public sector accounting using a bibliometric approach. A total of 58 Scopus-indexed articles published between 2017 and 2025 were analyzed using keyword co-occurrence and visualized through VOSviewer. The findings indicate a significant increase in publications, particularly during 2021–2025, reflecting growing academic interest. Computer science dominates the field, followed by business, management, and accounting, highlighting its multidisciplinary nature. Citation analysis reveals a mix of highly influential foundational studies and emerging recent works. However, collaboration networks among authors, institutions, and countries remain limited and not yet globally integrated. Keyword co-occurrence analysis shows blockchain as the central theme, with a shift from technical aspects toward applications in accounting, auditing, and governance. Overall, this research confirms that blockchain studies in the public sector are in a growth and maturation phase with substantial future potential.